A conspectus of neotropical lauxaniidae (Diptera: Lauxanioidea) - Gaimari, Stephen D.; Silva, Vera C. [UNESP] (Magnolia Press, 2020)
A fully annotated catalog of genus- and species-group names of Neotropical Lauxaniidae (Diptera: Lauxanioidea) is presented, providing details of references to these names in literature, and providing additional details such as distributions, generic combinations, synonymies, misspellings and emendations, information on types, notes on unusual situations, etc. As this catalog is meant to supplement the older Catalog of the Diptera of America North of Mexico, to complete the cataloging of the New World Lauxaniidae, “Neotropical” is herein inclusive of everything south of the United States, and the Nearctic parts of Mexico are not separately distinguished. The catalog is organized alphabetically within each of the three lauxaniid subfamilies, Eurychoromyiinae, Homoneurinae and Lauxaniinae, treating 91 available genus-group names, of which 77 represent valid genera. In the species-group, the catalog treats 441 available species-group names, of which 391 represent valid Neotropical lauxaniid species, 39 are invalid, three are valid but extralimital lauxaniids, five are valid but removed from Lauxaniidae, and two are new replacement names for two homonyms outside Lauxaniidae. The following nine new genera are described, based on previously described species: Elipolambda Gaimari & Silva (type species, Sapromyza lopesi Shewell, 1989), Griphoneuromima Silva & Gaimari (type species, Sapromyza frontalis Macquart, 1844b), Meraina Silva & Gaimari (type species, Lauxania ferdinandi Frey, 1919), Myzaprosa Gaimari & Silva (type species, Myzaprosa mallochi Gaimari & Silva), Paradeceia Silva & Gaimari (type species, Sapromyza sororia Williston, 1896b), Pseudodeceia Silva & Gaimari (type species, Lauxania leptoptera Frey, 1919), Sericominettia Gaimari & Silva (type species, Minettia argentiventris Malloch, 1928), Zamyprosa Gaimari & Silva (type species, Sapromyza semiatra Malloch, 1933), and Zargopsinettia Gaimari & Silva (type species, Minettia verticalis Malloch, 1928). The following four new replacement names in the species-group replace junior homonyms: Myzaprosa mallochi Gaimari & Silva (for Sapromyza spinigera Malloch, 1933, nec Malloch, 1925), Pseudogriphoneura mallochi Silva & Gaimari (for Minettia infuscata Malloch, 1928, nec Sciomyza infuscata Wulp, 1897), Xenochaetina hendeli Silva & Gaimari (for Allogriphoneura robusta Hendel, 1936, nec Helomyza robusta Walker, 1858), Zamyprosa macquarti Gaimari & Silva (for Sciomyza nigripes Blanchard, 1854, nec Sapromyza nigripes Macquart, 1844). The following six genus-group names are new synonyms: Allogriphoneura Hendel, 1925 (= Xenochaetina Malloch, 1923), Bacilloflagellomera Papp & Silva, 1995 (= Stenolauxania Malloch, 1926), Haakonia Curran, 1942 (= Xenochaetina Malloch, 1923), Homoeominettia Broadhead, 1989 (= Allominettia Hendel, 1925), Paraphysoclypeus Papp & Silva, 1995 (= Physoclypeus Hendel, 1907), Tibiominettia Hendel, 1936 (= Allominettia Hendel, 1925). The following 12 species-group names are new synonyms: Chaetocoelia banksi Curran, 1942 (= Chaetocoelia excepta (Walker, 1853)), Chaetocoelia tripunctata Malloch, 1926 (= Chaetocoelia excepta (Walker, 1853)), Minettia semifulva Malloch, 1933 (= Zamyprosa nigriventris (Blanchard, 1854)), Pseudogriphoneura scutellata Curran, 1934a (= Xenochaetina porcaria (Fabricius, 1805)), Sapromyza apta Walker, 1861 (= Chaetominettia mactans (Fabricius, 1787)), Sapromyza brasiliensis Walker, 1853 (= Chaetominettia corollae (Fabricius, 1805)), Sapromyza semiatra subsp. remissa Malloch, 1933 (= Zamyprosa semiatra (Malloch, 1933)), Sapromyza sordida Williston, 1896b (= Neogriphoneura sordida (Wiedemann, 1830)), Setulina geminata subsp. quadripunctata Malloch, 1941, subsp. tripunctata Malloch, 1941 & subsp. verticalis Malloch, 1941 (= Setulina geminata (Fabricius, 1805)), Tibiominettia setitibia Hendel, 1932 (= Allominettia assimilis (Malloch, 1926)). The following 96 lauxaniid species-group names are in new combinations: Allominettia approximata (Malloch, 1928; Deutominettia Hendel, 1925), Allominettia assimilis (Malloch, 1926; Minettia Robineau-Desvoidy, 1830), Allominettia rubescens (Macquart, 1844b; Sapromyza Fallén, 1810), Allominettia woldae (Broadhead, 1989; Homoeominettia Broadhead, 1989), Camptoprosopella sigma (Hendel, 1910; Procrita Hendel, 1908), Camptoprosopella verena (Becker, 1919; Sapromyza Fallén, 1810), Dryosapromyza pirioni (Malloch, 1933; Minettia Robineau-Desvoidy, 1830), Elipolambda duodecimvittata (Frey, 1919; Lauxania Latreille, 1804), Elipolambda lopesi (Shewell, 1989; Sapromyza Fallén, 1810), Elipolambda picrula (Williston, 1897; Sapromyza Fallén, 1810), Griphoneuromima frontalis (Macquart, 1844b; Sapromyza Fallén, 1810), Homoneura maculipennis (Loew, 1847; Sapromyza Fallén, 1810), Lauxanostegana albispina (Albuquerque, 1959; Steganopsis Meijere 1910), Marmarodeceia claripennis (Curran, 1934a; Pseudogriphoneura Hendel, 1907), Melanomyza nigerrima (Becker, 1919; Sapromyza Fallén, 1810), Meraina ferdinandi (Frey, 1919; Lauxania Latreille, 1804), Minettia altera (Curran, 1942; Pseudogriphoneura Hendel, 1907), Minettia duplicata (Lynch Arribálzaga, 1893; Sapromyza Fallén, 1810), Minettia lateritia (Rondani, 1863; Sapromyza Fallén, 1810), Minettia lupulinoides (Williston, 1897; Sapromyza Fallén, 1810), Minettia pallens (Blanchard, 1854; Sapromyza Fallén, 1810), Minettia remota (Thomson, 1869; Sapromyza Fallén, 1810), Minettia setosa (Thomson, 1869; Sapromyza Fallén, 1810), Myzaprosa chiloensis (Malloch, 1933; Sapromyza Fallén, 1810), Myzaprosa emmesa (Malloch, 1933; Sapromyza Fallén, 1810), Myzaprosa triloba (Malloch, 1933; Sapromyza Fallén, 1810), Neodecia albovittata (Loew, 1862; Lauxania Latreille, 1804), Neodecia bivittata (Curran, 1928b; Pseudogriphoneura Hendel, 1907), Neodecia flavipennis (Curran, 1928b; Pseudogriphoneura Hendel, 1907), Neodecia vittifacies (Curran, 1931; Pseudogriphoneura Hendel, 1907), Neominettia eronis (Curran, 1934a; Sapromyza Fallén, 1810), Neominettia lebasii (Macquart, 1844b; Sapromyza Fallén, 1810), Neominettia melanaspis (Wiedemann, 1830; Sciomyza Fallén, 1820d), Neoxangelina congruens (Hendel, 1910; Physegenua Macquart, 1848a/b), Neoxangelina facialis (Wiedemann, 1830; Sciomyza Fallén, 1820d), Neoxangelina flavipes (Hendel, 1926; Physegenua Macquart, 1848a/b), Paracestrotus albipes (Fabricius, 1805; Scatophaga Fabricius, 1805), Paradeceia incidens (Curran, 1934a; Sapromyza Fallén, 1810), Paradeceia shannoni (Malloch, 1933; Sapromyza Fallén, 1810), Paradeceia sororia (Williston, 1896b; Sapromyza Fallén, 1810), Physegenua annulata (Macquart, 1844b; Ephydra Fallén, 1810), Physoclypeus nigropleura (Papp & Silva, 1995; Paraphysoclypeus Papp & Silva, 1995), Poecilohetaerus suavis (Loew, 1847; Sapromyza Fallén, 1810), Poecilolycia blanchardi (Malloch, 1933; Sapromyza Fallén, 1810), Poecilolycia lineatocollis (Blanchard, 1854; Sapromyza Fallén, 1810), Poecilominettia aibonito (Curran, 1926; Minettia Robineau-Desvoidy, 1830), Poecilominettia bipunctata (Say, 1829; Sapromyza Fallén, 1810), Poecilominettia evittata (Malloch, 1926; Minettia Robineau-Desvoidy, 1830), Poecilominettia mona (Curran, 1926; Minettia Robineau-Desvoidy, 1830), Poecilominettia nigropunctata (Malloch, 1928; Minettia Robineau-Desvoidy, 1830), Poecilominettia plantaris (Thomson, 1869; Sapromyza Fallén, 1810), Poecilominettia quichuana (Brèthes, 1922; Sapromyza Fallén, 1810), Poecilominettia schwarzi (Malloch, 1928; Sapromyza Fallén, 1810), Poecilominettia sonax (Giglio-Tos, 1893; Sapromyza Fallén, 1810), Poecilominettia thomsonii (Lynch-Arribálzaga, 1893; Sapromyza Fallén, 1810), Poecilominettia triseriata (Coquillett, 1904a; Sapromyza Fallén, 1810), Pseudocalliope albomarginata (Malloch, 1933; Minettia Robineau-Desvoidy, 1830), Pseudodeceia leptoptera (Frey, 1919; Lauxania Latreille, 1804), Pseudogriphoneura albipes (Wiedemann, 1830; Lauxania Latreille, 1804), Pseudominettia argyrostoma (Wiedemann, 1830; Lauxania Latreille, 1804), Ritaemyia unifasciata (Macquart, 1835; Tephritis Latreille, 1804), Sciosapromyza fuscinervis (Malloch, 1926; Minettia Robineau-Desvoidy, 1830), Sciosapromyza limbinerva (Rondani, 1848; Sapromyza Fallén, 1810), Sciosapromyza scropharia (Fabricius, 1805; Scatophaga Fabricius, 1805), Scutominettia guyanensis (Macquart, 1844b; Sapromyza Fallén, 1810), Sericominettia argentiventris (Malloch, 1928; Minettia Robineau-Desvoidy, 1830), Sericominettia aries (Curran, 1942; Pseudogriphoneura Hendel, 1907), Sericominettia holosericea (Fabricius, 1805; Scatophaga Fabricius, 1805), Sericominettia nigra (Curran, 1934a; Pseudogriphoneura Hendel, 1907), Sericominettia velutina (Walker, 1853; Helomyza Fallén, 1820a), Stenolauxania flava (Silva, 1999a; Bacilloflagellomera Papp & Silva, 1995), Stenolauxania fusca (Silva, 1999a; Bacilloflagellomera Papp & Silva, 1995), Stenolauxania longicornus (Silva, 1999a; Bacilloflagellomera Papp & Silva, 1995), Stenolauxania nigrifemuris (Silva, 1999a; Bacilloflagellomera Papp & Silva, 1995), Stenolauxania pectinicornis (Papp & Silva, 1995; Bacilloflagellomera Papp & Silva, 1995), Trivialia nigrifrontata (Becker, 1919; Sapromyza Fallén, 1810), Trivialia scutellaris (Williston, 1896b; Phortica Schiner, 1862), Trivialia venusta (Williston, 1896b; Sapromyza Fallén, 1810), Xenochaetina annuliventris (Hendel, 1926; Allogriphoneura Hendel, 1925), Xenochaetina glabella (Becker, 1895; Lauxania Latreille, 1804), Xenochaetina nigra (Williston, 1896b; Physegenua Macquart, 1848a/ b), Xenochaetina phacosoma (Hendel, 1926; Allogriphoneura Hendel, 1925), Xenochaetina porcaria (Fabricius, 1805; Scatophaga Fabricius, 1805), Xenochaetina robusta (Walker, 1858; Helomyza Fallén, 1820a), Zamyprosa dichroa (Malloch, 1933; Minettia Robineau-Desvoidy, 1830).
Keywords: Chloropidae; Distribution; Heleomyzidae; Homonym; Lectotype designation; New combination; New genus; New name; New synonym; Nomenclature; Platystomatidae; Sciomyzidae; Type deposition; Type locality